Raising awareness of the Macmillan Durham cachexia pack (MDCP) within a local cancer network. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Hawkins, Colette; Andrew, Inga
Abstract : Background: The Macmillan Durham Cachexia Pack (MDCP) was launched in 2007. In 2010, in response to sporadic awareness and use of MDCP within The North of England Cancer Network (NECN), a series of workshops were commissioned to raise awareness. Aim: To raise awareness of MDCP, ascertain barriers to its use and establish its role in practice. Method: Three workshops took place at different venues within NECN. The structure of each workshop was; sharing views on participants' experience of caring for patients with ACS, case presentation to highlight common issues, review of the MDCP and discussion around opportunities and barriers to use of the MDCP. Results: Of the 46 participants, most were nursing staff with a wide range of healthcare professionals and allied staff represented. Views from participants' experience of patients with ACS largely corresponded with the literature; a feeling of helplessness/hopelessness when approaching patients, finding ACS difficult/hard/challenging, patients reporting powerlessness/desperation but appreciating support to cope with symptoms and to change expectations. Opportunities from use of MDCP included; ensures a consistent approach for generalist staff, resource to use in education sessions including for carers, can be adapted to local policy and need, useful tool for immediately after diagnosis. Barriers to use of MDCP included; changing patients attitudes that something can be done about ACS, lack of flexibility with hospital catering, time constraints, responsibility for assessing patients, number of other assessment tools requiring completion. Conclusion: The workshops were reported to be useful and achieved the aim of raising awareness of MDCP. It appears that the future of MDCP lies as an educational tool to enable specialists to improve awareness and management of ACS and as a practical tool for generalists from all related professions, to dip in and out of.